Information and Communication Technology (ICT) in the Service of Multiculturalism - Hoter, Elaine; Shonfeld, Miri; Ganayim, Asmaa (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper presents an online inter-group contact hypothesis (OICH) model, developed within the Israel education system, whereby online and distance learning (ODL) is used in the service of multiculturalism. The goal is to build bridges among secular and religious Arabs and Jews in Israel based on small multicultural groups and collaborative learning through effective use of the Internet and other cutting-edge information technologies. The model expands the contact hypothesis (which holds that under the right conditions contact could reduce bias between groups) to a model for online collaboration. It adds the gradual development of contact between the groups by progressing from individual asynchronous textual communication to individual synchronous audio communication combined with collaborative asynchronous communication to collaborative synchronous communication and finally to face-to-face communication.